During the COVID-19 Epidemic: Recommendations for the Admission and Treatment of Patients With Ovarian Cancer - Ling, Yu; Mingxia, Ye; Xiaoyan, Zhang; Yifan, Fan; Peipei, Liu; Yue, Zhang; Yuanguang, Meng; Lian, Li (Frontiers in Surgery, 2021)
Background: The coronavirus disease 2019 (COVID-19) had become a health care event endangering humans globally. It takes up a large number of healthcare resources. We studied the impact of COVID-19 on patients with ovarian cancer by comprehensively analyzing their admissions before and after the epidemic, and made reasonable suggestions to improve their current situation. Methods: We randomly divided the enrolled patients into three groups, PreCOVID-19 Group (PCG) (2019.8.20–2020.1.20), COVID-19 Group (CG) (2020.1.21–2020.6.14), and Secondary Outbreak COVID-19 Group (SOCG) (2020.6.15–2020.10.10). One-way ANOVA and chi-square test were used for analysis. Results: The number of patients from other provinces decreased significantly (p < 0.05). The total hospital stay during the epidemic was substantially more extended (p < 0.05). Before the epidemic, our department performed more open surgery while during the epidemic outbreak, we tended to choose laparoscopy (p < 0.01). We took a longer surgery time (P < 0.05). Patients had significantly less post-operative fever during the epidemic (p < 0.001). Conclusion: During the COVID-19 epidemic, no patient was infected with COVID-19, and no patient experienced severe post-operative complications. We recommend maintaining the admissions of patients with ovarian cancer during the epidemic following the rules: 1. The outpatients must complete a nucleic acid test and chest CT in the outpatient clinic; 2. Maintain full daily disinfection of the ward and insist that health care workers disinfect their hands after contact with patients; 3. Increase the use of minimally invasive procedures, including laparoscopy and robotics; 4. Disinfect the ward twice a day with UV light and sodium hypochlorite disinfectant; 5. Patients need to undergo at least three nucleic acid tests before entering the operating room.